Home as a Working Place: Expressing the Perception of Work-Life Balance in the Global Epidemic Period - Vatansever, Çiğdem; Sezer, Meltem; Ünsever, Ayça (Border Crossing, 2021)
The basic questions of this research are how and to what extent the adaptation to the "home" as a new work space, and how the work and non-work life balance is experienced during the global epidemic period. The effects of working spaces on our health and well-being, as “individual living spaces” that are affected by the physical and social environment and also affect our perceptions of the psychological environment, are among the issues that have been emphasized in recent years. With the Covid 19 pandemic; remote working has become the norm around the world, especially for office workers. With the transition to working at home, the lines and distances between work and office areas have begun to blur gradually. As a result of this transition, creating a private space in the home has become important. Our study deals with the multidisciplinary subject "home as a workplace" in the context of the relationship between the individual and the environment. For this purpose, posts about working from home on a social networking platform were evaluated with content analysis. The findings were presented over the themes formed as a result of content analysis, with indicators such as time interval, gender, job-occupation, demographics and organization of the work area, institutionalism, life balance. The findings show that the posts on the subject are mostly positive, the majority of those who share are women, and from the beginning of the epidemic, arranging the daily routine at home and creating a working area are priority issues.